Decision analysis for secondline maintenance treatment of platinum sensitive recurrent ovarian cancer: a review. Issue 5 (19th February 2020) - Arend, Rebecca; Westin, Shannon Neville; Coleman, Robert L
Abstract : Most women with ovarian cancer experience disease relapse, presenting numerous treatment challenges for clinicians. Maintenance therapy in the relapsed setting aims to extend the time taken for a cancer to progress, thus delaying the need for additional treatments. Four therapies are currently approved in the USA for secondline maintenance treatment of platinum sensitive, recurrent ovarian cancer: one antivascular endothelial growth factor agent (bevacizumab) and three poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors (olaparib, niraparib, and rucaparib). In addition to efficacy, maintenance therapies must have a good tolerability profile and no significant detrimental impact on quality of life, as patients who receive maintenance are generally free from cancer related symptoms. Data from key bevacizumab trials (OCEANS, NCT00434642 ; GOG-0213, NCT00565851 ; MITO16B, NCT01802749 ) and PARP inhibitor trials (Study 19, NCT00753545 ; SOLO2, NCT01874353 ; NOVA, NCT01847274 ; ARIEL3, NCT01968213 ) indicate that bevacizumab and the PARP inhibitors are effective in patients with platinum sensitive, recurrent ovarian cancer but differ in their tolerability profiles. In addition, the efficacy of PARP inhibitors is dependent on the presence of homologous recombination repair deficiency, with patients with the deficiency experiencing greater responses from treatment compared with those who are homologous recombination repair proficient. Allowing for caveats of cross trial comparisons, we advise that clinicians account for the following points when choosing whether and when to administer a secondline maintenance treatment for a specific patient: presence of a homologous recombination repair deficient tumor; the patient's baseline characteristics, such as platelet count and blood pressure; mode of administration of therapy; and consideration of future treatment options for thirdline and later therapy.